2003
DOI: 10.1021/es020229+
|View full text |Cite
|
Sign up to set email alerts
|

Biomagnification Study on Organochlorine Compounds in Marine Aquaculture:  The Sea Bass (Dicentrarchus labrax) as a Model

Abstract: Biomagnification of organochlorine compounds (pesticides and polychlorinated biphenyls) through the marine aquaculture food chain is investigated. From first-feeding, specimens of sea bass were exposed to commercial fish feed (that contained DDTs and PCBs residues) for ca. 24 months, and selected tissues (white and red muscle, liver, and visceral fat) were analyzed after 6 and 24 months of diet exposure. Data obtained showed that experimental fish tissues presented a similar contamination pattern to that of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 31 publications
2
15
0
1
Order By: Relevance
“…Levels previously reported for PCB 153 in salmon and sea-bass feed are within the feed results (51-53 ng g À1 , lipid). 8.4-23.8 ng g À1 , lipid, in Jacobs et al (2002); 17-35.8 ng g À1 , lipid, in Serrano et al (2003). The ratio of p,p 0 -DDE to p,p 0 -DDT was 6.5 in oil and lower in pellets, indicating most likely differing sources of pesticides in pellets than the actual oil analysed, or that other ingredients are contributing to the presence of these pesticides in pellets.…”
Section: Contaminants and Lipid In Feedmentioning
confidence: 89%
See 1 more Smart Citation
“…Levels previously reported for PCB 153 in salmon and sea-bass feed are within the feed results (51-53 ng g À1 , lipid). 8.4-23.8 ng g À1 , lipid, in Jacobs et al (2002); 17-35.8 ng g À1 , lipid, in Serrano et al (2003). The ratio of p,p 0 -DDE to p,p 0 -DDT was 6.5 in oil and lower in pellets, indicating most likely differing sources of pesticides in pellets than the actual oil analysed, or that other ingredients are contributing to the presence of these pesticides in pellets.…”
Section: Contaminants and Lipid In Feedmentioning
confidence: 89%
“…The health-related advantages of providing consumers with food rich in omega-3 fatty acids is well recognized (Castell, 1988). Few studies have determined the level of contaminants in aquaculture fish (Lung et al, 2003;Serrano et al, 2003;Hites et al, 2004; Danish Website Foedevaredirektoratet.dk/fdir/publications/2001018/rapport.txt) and these can be higher than in the wild. The farming of sea animals will only increase with time; therefore, levels of contaminants should be minimized to increase the value of this relatively anthropogenic link in the food chain.…”
Section: Uptake From Feedmentioning
confidence: 99%
“…They concluded that the load of organochlorine pollutants in fish tissues is related to seasonal changes in the feeding behaviour of the species and their feeds (Serrano et al 2008). The fish diets stand out as an important source of organic persistent contaminants (Serrano et al 2003, Nácher-Mestre et al 2009). The distribution of the PCB congener in tissues of sea bass collected in two fish farms in Ria de Aveiro resembled that of fish fed a pelleted diet, suggesting that a commercial diet is a major source of PCBs (Antunes and Gil 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In farmed rainbow trout, the dietary retention of sum chlordane (cis-trans and oxychlordane) and sum toxaphene in the edible part of market-size fi sh was approximately 33 and 27%, respectively (Karl et al, 2002). In commercially reared sea bream (Dicentrarchus labrax) biomagnifi cation of DDTs and HCB from feed to muscle has been shown to occur (Serrano et al, 2003). In cultured Asian seabass (Lates calcarifer), 15% of DDT and its metabolites are partitioned in muscle (Bayen et al, 2005).…”
Section: Carry-over Of Pops To Edible Tissue and Preventionmentioning
confidence: 99%